An investigation on the in situ synthesis–sintering and mechanical properties of MoSi2–xSiC composites prepared by spark plasma sintering. (January 2015) - Esmaeily, Soheila; Kermani, Milad; Razavi, Mansour; Rahimipour, Mohammad Reza; Zakeri, Mohammad
Abstract: Composites of MoSi2 –x wt.% SiC (x = 5, 10, 15, 20) prepared using spark plasma sintering. The effect of temperature on the in-situ synthesis–sintering was investigated between 1100 °C and 1500 °C. X-ray diffraction patterns showed that at 1100 °C the reactions were incomplete and elementary diffraction peaks of Mo, Si and C still exist. With an increase in temperature from 1100 to 1300 °C the reactions were performed completely. The study showed that the sintering ability at higher temperature at the presence of enough mechanical pressure was better because the heat released from the reaction between Mo, Si and C causes higher temperature than the melting point of Si (1410 °C). Consequently the silicon would melt during the heating process. The molten Si can strengthen the interconnections and it has higher diffusion rate. Therefore, due to the liquid phase sintering and at the presence of mechanical pressure, the sintering ability at higher temperature is better than lower temperature. Scanning electron microscopy showed that with the addition of carbon, there was no silica phase in the microstructure of the synthesized samples, due to the formation of SiC. Therefore, it can be noted that the addition of carbon leads to better mechanical properties due to elimination of silica phase. Highlights: MoSi2–x wt.% SiC (x = 5, 10, 15 and 20) composites prepared using spark plasma sintering and Mo, Si and C powders The XRD results showed that at 1100 °C the reactions did not perform completely. The increase in temperature did not cause a significant improvement in the density of the samples. The increase in the amount of SiC addition resulted in better mechanical properties.